Critical properties of laminated rubber bearings including the effect of eccentric vertical loading. Issue 4 (March 2021) - Zhou, Fangyuan; Wu, Dongdong; Zhou, Lemu; Zhu, Hongping
The critical properties of laminated rubber bearings including the effect of eccentric vertical loading are investigated in this article. The critical load, horizontal critical displacement, and vertical displacement of the laminated rubber bearing including an initial eccentric vertical loading are compared with those of the laminated rubber bearing under axial vertical loading. The comparison results show that the critical load and the horizontal critical displacement decrease with the increase in the eccentricity of the vertical loading when the laminated rubber bearing moves into the side where the vertical load acts (" positive side "), whereas they increase in the opposite side (" negative side "). The vertical displacement in the " positive side " increases with the increase in the eccentricity of the vertical loading, whereas that in the " negative side " decreases. Moreover, the vertical displacement of the laminated rubber bearing in the " positive side " is larger than that in the " negative side ."